The challenge of anglicisms - Yahiaoui, Zoubir (El Omda in Linguistics and Discourse Analysis, 2023)
Anglicisms have left a lasting mark on the history of the French language in the 20th century, insofar as most borrowings in French are of English origin. In response to this linguistic phenomenon, various strategies have been developed to address it. However, the success of these strategies has been mixed and often limited. Consequently, selective criteria have been established to distinguish between anglicisms considered beneficial and those deemed detrimental to the French language.